2023
DOI: 10.5489/cuaj.8254
|View full text |Cite
|
Sign up to set email alerts
|

The impact of tranexamic acid on perioperative outcomes in urological surgeries: A systematic review and meta-analysis

Abstract: Introduction: Tranexamic acid (TXA) is an antifibrinolytic agent widely used in surgery to decrease bleeding and reduce the need for blood product transfusion. The role of TXA in urology is not well summarized. We conducted a systematic review of studies reporting outcomes of TXA use in urological surgery. Methods: A comprehensive search was conducted from the following databases: PubMed, Embase, Cochrane Library, and Web of Science. Two reviewers performed title and abstract screening, full text review, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 65 publications
(54 reference statements)
0
0
0
Order By: Relevance
“…While several historical studies have focused on reduction in tract size to decrease bleeding risk (18) more recent studies have evaluated pharmacologic treatment with tranexamic acid to reduce bleeding risk (19). Recent metaanalyses and review articles assessing the use of systemic TXA have demonstrated significant decreases in post-PCNL bleeding and transfusion rates with the use of this medication (20,21)and a recent RCT published looking at the use of TXA for complex PCNL demonstrated decreased transfusion and improved stone clearance (19). In the current study, we sought to add to the literature by utilizing a novel statistical method to evaluate the effects of TXA during PCNL (Bayesian network meta-analysis and meta-regression) as well as included TXA irrigation (TXA-I) in addition to systemic TXA (TXA-S) in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…While several historical studies have focused on reduction in tract size to decrease bleeding risk (18) more recent studies have evaluated pharmacologic treatment with tranexamic acid to reduce bleeding risk (19). Recent metaanalyses and review articles assessing the use of systemic TXA have demonstrated significant decreases in post-PCNL bleeding and transfusion rates with the use of this medication (20,21)and a recent RCT published looking at the use of TXA for complex PCNL demonstrated decreased transfusion and improved stone clearance (19). In the current study, we sought to add to the literature by utilizing a novel statistical method to evaluate the effects of TXA during PCNL (Bayesian network meta-analysis and meta-regression) as well as included TXA irrigation (TXA-I) in addition to systemic TXA (TXA-S) in the analysis.…”
Section: Discussionmentioning
confidence: 99%